2019
DOI: 10.3390/ijerph16234811
|View full text |Cite
|
Sign up to set email alerts
|

Developing a New Spectral Index for Detecting Cadmium-Induced Stress in Rice on a Regional Scale

Abstract: In natural farmland ecosystems, cadmium (Cd) pollution in rice has attracted increasing attention because of its high toxicity, relative mobility, and high water solubility. This study aims to develop a spectral index for detecting Cd stress in rice on a regional scale. Three experimental sites are selected in Zhuzhou City, Hunan Province. The hyperspectral data, chlorophyll (Chl) content, leaf area index, average leaf angle, Cd concentration in soil, and Sentinel-2A images from 2017 and 2018 are collected. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…03725/B/SK/VII/89, the maximum threshold value of heavy metal contamination in fish for pollutants Pb +2 and Cu +2 = 0.008 µg/g [33,55,82,101] The data on the average concentrations of the two heavy metal pollutants (Table 7) show that exposure to Pb +2 and Cu +2 is still below the threshold value. However, using the Australian and New Zealand Environment and Conservation Council (ANZECC) standard, with a smaller tolerance value than the maximum threshold, it was concluded that the two pollutants found in fish around BCI exceeded the standard [10,55,76,102,103]. Based on the data, Table 7 shows that all types of samples (fish, sponges, seawater, and sediments) obtained in the waters around BCI have exceeded the maximum threshold value specified [4,10,48,104].…”
Section: Heavy Metal Pollutant Analysismentioning
confidence: 99%
“…03725/B/SK/VII/89, the maximum threshold value of heavy metal contamination in fish for pollutants Pb +2 and Cu +2 = 0.008 µg/g [33,55,82,101] The data on the average concentrations of the two heavy metal pollutants (Table 7) show that exposure to Pb +2 and Cu +2 is still below the threshold value. However, using the Australian and New Zealand Environment and Conservation Council (ANZECC) standard, with a smaller tolerance value than the maximum threshold, it was concluded that the two pollutants found in fish around BCI exceeded the standard [10,55,76,102,103]. Based on the data, Table 7 shows that all types of samples (fish, sponges, seawater, and sediments) obtained in the waters around BCI have exceeded the maximum threshold value specified [4,10,48,104].…”
Section: Heavy Metal Pollutant Analysismentioning
confidence: 99%
“…The average concentration of the two types of heavy metal pollutants (Table 7) shows that exposure to Pb +2 and Cu +2 is still below the threshold value. However, using the Australian and New Zealand Environment and Conservation Council (ANZECC) standard with a tolerance value of the smaller the maximum threshold, it was concluded that the two types of pollutants found in fish around BCI had exceeded the standard [101,102] The exposure concentration of Pb +2 in fish obtained from ST 1 (2.4517 g/g) was found to have exceeded the maximum threshold [103]. It is understandable and quite rational because consumption patterns, activities, and dynamics in each type of marine fish vary greatly.…”
Section: Heavy Metal Pollutant Analysismentioning
confidence: 99%
“…Accurate identification and monitoring of such stress can not only provide reasonable suggestions for the safe production of rice, but also protect human health to some extent. Remote sensing technology represents an efficient and economical means for monitoring and assessing heavy metal pollution in rice on a large scale [ 1 ]. However, in natural farmland ecosystems, changes in the physiological indicators of crop growth appear similar under different types of stresses (heavy metal stress, pest, and disease stress), making it difficult to accurately identify heavy metal stress [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%